If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x + -13 = 72 Reorder the terms: -13 + x = 72 Solving -13 + x = 72 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '13' to each side of the equation. -13 + 13 + x = 72 + 13 Combine like terms: -13 + 13 = 0 0 + x = 72 + 13 x = 72 + 13 Combine like terms: 72 + 13 = 85 x = 85 Simplifying x = 85
| 0.11-0.03(x+3)=-0.04(3-x) | | 5x-179=61-10x | | 19.7=21.6+f | | 5.5x+6x=37 | | v^2+15v+44=0 | | 0.3z-3-0.5z=-6 | | 15h-42=-6h-39 | | log(4)*(5x+3)=1 | | r=9cm | | -6x+7=5x+40 | | m^2+m-35=0 | | 7t^2-22t+7=0 | | (x+20)+3x=90 | | 2x+4(x-3)=12 | | 12=-7+v | | -56-6x-5x=43 | | -16t^2-11t+120=0 | | -16t^2-11t+120=h | | 14+23= | | 0=8-3(6-6x) | | .5y+(2x+5)=180 | | f(3)=12+3x | | s+8=-13.5 | | 4x-6x-7=7 | | 2x+9+7x-4=4x+7 | | 11x-154=-5x+54 | | 3(2y-3)=5(y+4) | | 30+8+7+10+25-4+9+25-3+6-5=108 | | x^2+2x-15=15 | | H+9.7=-9 | | x^3-2x^2-41x-56=0 | | 3xy+2x=4y |